Rethinking Higher Education: Integration as a Framework for Change. Issue 185 (5th March 2019) - Birx, Donald L.
Abstract: This chapter discusses the overhaul of Plymouth State University using a framework of integration in all matters of decision‐making. This is an example of whole system reorganization where traditional independent structures have been replaced by integrated structures representing new ways of working together and integral experiences for students.